Simulation of the Security Assessment Information Leakage Channel Method Based on the Speech Signal Envelope - V. K. Zheleznyak; Y. R. Adamovskiy; A. G. Filipovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A method of information leakage channel security estimating based on the test speech signal envelope cross-correlation analysis is proposed and its includes: test signal generating and extracting its envelope, emitting and measuring in a leakage channel, extracting the resulting signal envelope, calculating the correlation coefficient between the original and received envelopes, and comparing with a threshold value. A metod for extracting a low-frequency signal envelope using the Hilbert transform is shown. A description of the cross-correlation analysis based on the Pearson correlation coefficient is given. The leakage channel simulation modeling, formation and measurement of the test signals was performed in the MatLab. The obtained results confirm the greater efficiency of using the envelope compared to the original signal, and demonstrate the speech signals advantage over harmonic signals as test signals for assessing the information leakage channel security.